Cost-effectiveness analysis of quadrivalent seasonal influenza vaccines in Beijing: A modeling analysis. Issue 7 (11th February 2022) - Zhu, Dawei; Lv, Min; Bai, Yunhua; Wu, Jiang; He, Ping
Highlights: We explored eight scenarios of QIV vs. TIV using a decision tree model to simulate the health and economic impact of the introduction of QIV to school children, elderly adults, and health care workers in Beijing. The main health benefits of the introduction of QIV are the decrease in infections and hospitalization among school children, as well as hospitalization and death among elderly adults. The introduction of QIVs to school children, elderly adults, and health care workers is likely to be cost-effective, either separately or collectively. Abstract: Background: Since 2007, Beijing has offered a free trivalent influenza vaccine (TIV) for residents aged ≥ 60 years and school students. The quadrivalent influenza vaccine (QIV) was administered to school children in 2018 and will be administered to elderly adults in the future. In addition, health care workers (HCWs) who are involved in the prevention and control of COVID-19 were included in the program in 2020. This study aimed to analyze the cost-effectiveness of a comprehensive list of combined strategies of TIV and QIV for school children, elderly adults, and HCWs to identify the most cost-effective strategy. Methods: A decision tree was developed to compare 1-year outcomes of TIV vs. QIV in three risk groups: school children, elderly adults, and HCWs. The outcome was incremental cost per quality-adjusted life-year (QALY). Probabilistic sensitivity analyses and scenario analyses were developed to assess the robustness of the results. Results: From the perspective of society, this study found that the introduction of QIVs can be cost-effective for any and all targeted groups with a willingness-to-pay threshold of 3-fold GDP per capita. Among all programs, program H (all school children, elderly adults, and HCWs received the QIV) showed a 79% probability of being cost-effective with an incremental cost-effectiveness ratio (ICER) of 13, 580 (95% CI: 13, 294, 13, 867) US$/QALY and was the preferred option in the base case scenario. Conclusion: The introduction of QIVs to school children, elderly adults, or HCWs is likely to be cost-effective, either separately or collectively. The introduction of QIV to school children, elderly adults, and health care workers simultaneously showed the highest probability of being cost-effective and was the preferred option.